2015
DOI: 10.1177/0163443714566903
|View full text |Cite
|
Sign up to set email alerts
|

The ongoing significance of national media systems in the context of media globalization

Abstract: This article argues that the concept of national media systems, and the comparative study of media systems, institutions, and practices, retains relevance in an era of media globalization and technological convergence. It considers various critiques of 'media systems' theories, such as those which view the concept of 'system' as a legacy of an outdated positivism and those which argue that the media globalization is weakening the relevance of nation-states in structuring the field of media cultures and practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 33 publications
0
50
0
4
Order By: Relevance
“…We aimed to identify initiatives and practices that could grant communication rights to marginalized groups and promote a democratic, inclusive and plural media landscape, which is an important aspect of social and political representation (Fraser, 2009). In a critique of the goals and actions proposed by WSIS, we argued that they put too much focus on providing technologies to individuals, rather than creating public policies that Finally, we argue with Flew and Waisbord (2015) that even in the current reality of globalized markets and international communication and information flows, the national sphere is still important in media development. Communication, as multifaceted and complex practices and processes, unfolds within the framework of society, politics and culture, and these are, despite upholding virtues of a global citizenship, anchored in national and local symbolic universes and imaginaries.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…We aimed to identify initiatives and practices that could grant communication rights to marginalized groups and promote a democratic, inclusive and plural media landscape, which is an important aspect of social and political representation (Fraser, 2009). In a critique of the goals and actions proposed by WSIS, we argued that they put too much focus on providing technologies to individuals, rather than creating public policies that Finally, we argue with Flew and Waisbord (2015) that even in the current reality of globalized markets and international communication and information flows, the national sphere is still important in media development. Communication, as multifaceted and complex practices and processes, unfolds within the framework of society, politics and culture, and these are, despite upholding virtues of a global citizenship, anchored in national and local symbolic universes and imaginaries.…”
Section: Resultsmentioning
confidence: 94%
“…Modernization was no longer viewed as a desired goal that followed a linear process and evolved equally in all nations. It became clear that the positivist models of development, in overlooking the role that native cultures played for societies of the South, had failed to consider the context in which modernizing variables such as urbanization, literacy, mass media use, and democratic participation were applied (Flew & Waisbord, 2015;Melkote, 1991Melkote, , 2003Narula & Pearce, 1986;Rogers, 1976;Stevenson, 1998).…”
Section: Development -Outside Of Context?mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, scholars have advanced numerous persuasive arguments for the likelihood of a convergence of news contents (e.g., Boyd‐Barrett, ; Cottle, ; Hallin & Mancini, ). At the same time, recent empirical evidence has challenged some of these expectations, documenting enduring differences, and even new divergences in media system characteristics (Nielsen, ) or national media policies (Flew & Waisbord, ). Umbricht and Esser () have shown that even a common tendency toward popularization does not necessarily result in a convergence of news contents.…”
mentioning
confidence: 99%